Vulnerability to a just transition in coal-intensive provinces in Turkey - Kizilkaya, Simay; Aksoy, Tolga (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
This study assesses the potential social vulnerabilities of Turkish provinces during the coal phase-out process. Provinces heavily reliant on coal and lignite mining activities will likely face significant socio-economic challenges during this energy transition. A vulnerability assessment indicates that coal-intensive provinces are at heightened risk, with substantial spatial interdependence among them, as neighboring provinces share similar vulnerabilities due to their reliance on coal-fired electricity generation. Without careful management, these provinces could disproportionately experience negative impacts, including unemployment and economic deterioration. The findings highlight the critical importance of inclusive strategies addressing national and regional disparities, and fostering a just and sustainable energy shift.
Keywords: Coal phase-out; just transition; provincial social vulnerability; spatial dependence; POLICY; Area Studies